HUBUNGAN KETEHANAN PANGAN KELUARGA DAN TINGKAT KECUKUPAN ZAT GIZI DENGAN KEJADIAN STUNTING PADA ANAK USIA 24-59 BULAN DI DAERAH PESISIR (Studi di Wilayah Kerja Puskesmas Bandarharjo Kota Semarang) - Rohmatul Bariroh Al Faiqoh; Suyatno Suyatno; Apoina Kartini (Jurnal Kesehatan Masyarakat (Undip), 2018)
Family food security (food availability, accessibility, utilization, and diversity) are indirect causes related with stunting of children, while EER and EPR is a direct causal factors related with stunting of children. The purpose of this research was to analyze the correlation of household food security and the level of adequacy of nutrients with stunting in children aged 24-59 months in the coastal area of Semarang City. This type of research is an analytical survey using a cross sectional approach. The population in the study were all mothers who have children aged 24-59 months. The sample was chosen by purposive sampling method. Bivariate analysis using correlation Pearson and Rank Spearman test. Multivariate analysis using Linear Regression Test with Dummy Variable. The results of bivariate analysis showed that there was a correlation between food availability with EER, EPR and HAZ (p <0.05), food access with EPR, and HAZ (p <0, 05), food utilization with EER, EPR and HAZ (p <0.05), food diversity with EPR (p <0.05), EER and EPR with HAZ. The results of multivariate analysis showed that food availability was the variable that was most related to the HAZ (smallest significant). It was suggested that the community can utilize existing resources to fulfill family needs and increasing socio-economic conditions, so that family food security can be completely.